Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fmed.2022.878218
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Acupuncture on Symptomatic Improvement in Primary Sjögren’s Syndrome: A Randomized Controlled Trial

Abstract: AimWe sought to evaluate the efficacy of acupuncture in treating the main symptoms of primary Sjögren’s syndrome, specifically dryness, pain, and fatigue.MethodsA total of 120 patients with primary Sjögren’s syndrome were randomized in a parallel-group, controlled trial. Participants received acupuncture or sham acupuncture for the first 8 weeks, then were followed for 16 weeks thereafter. The primary outcome was the proportion of participants with a ≥ 30% reduction in ≥ 2 of 3 numeric analog scale scores for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…The unsatisfactory results of many SS treatments have led many doctors and patients to try acupuncture. SS disease is caused by an immune balance disorder and previous reports, including the current study, have confirmed the therapeutic effect of acupuncture on this syndrome (Liu et al, 2017;Zhou et al, 2022). While the mechanism by which acupuncture affects SS remains unclear, studies indicate that this treatment stimulates the production of innate immune cytokines such as IL-1, IL-6, IL-18, and TNFα, and adaptive immune cytokines including IL-2, IFN-, IL-5, IL-10, and IL-17, to initiate an immune response and repair rheumatoid arthritis (RA)-related injury (Dong et al, 2018;Du et al, 2019;Li et al, 2021;Su et al, 2019;Xu et al, 2018;Yu et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The unsatisfactory results of many SS treatments have led many doctors and patients to try acupuncture. SS disease is caused by an immune balance disorder and previous reports, including the current study, have confirmed the therapeutic effect of acupuncture on this syndrome (Liu et al, 2017;Zhou et al, 2022). While the mechanism by which acupuncture affects SS remains unclear, studies indicate that this treatment stimulates the production of innate immune cytokines such as IL-1, IL-6, IL-18, and TNFα, and adaptive immune cytokines including IL-2, IFN-, IL-5, IL-10, and IL-17, to initiate an immune response and repair rheumatoid arthritis (RA)-related injury (Dong et al, 2018;Du et al, 2019;Li et al, 2021;Su et al, 2019;Xu et al, 2018;Yu et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…The mean NAS score at Weeks 2–8 was used as the primary endpoint, while the mean score at Week 0 was considered the baseline score. The methods and evidence required to establish a ≥30% improvement in at least two of the three measures is closely related to clinical efficacy and are consistent with previous clinical trial study findings (Jiang et al, 2017; Ng & Bowman, 2010; Zhou et al, 2022). Serum IL‐17, TNF‐ɑ, and anti‐AQP1, 5, 8, and 9 antibody expression levels changed between Week 0 and Week 8 after the intervention.…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…In the prospective study titled “Efficacy and safety of acupuncture on symptomatic improvement in primary Sjögren's syndrome: a randomized controlled trial” ( 1 ), Prof. Jiang and colleagues evaluated acupuncture treatment of the main symptoms of primary Sjögren's syndrome (pSS), specifically dryness, pain, and fatigue. Their results suggested that acupuncture did not improve these symptoms more than a placebo did.…”
mentioning
confidence: 99%
“…Speci cally with regard to xerostomia in patients with SS, there is a meta-analysis in 2019 discussing different kinds of pharmacological therapies and found out that interferon -α 150IU thrice daily and cevimeline 30mg thrice daily had considerable therapeutic effect and the former was proven to be effective in increasing salivary ow rate attributing to its immunomodulatory action [31]. Nonetheless, there has been none review or meta-analysis speci cally focusing on xerostomia induced by SS under intervention of acupuncture while new clinical trials have been conducted and published with acupuncture on xerostomia in SS patients [32]. Therefore, with direct and indirect comparisons between different types of acupuncture, an up-to-date systematic review and network meta-analysis is in urgent need.…”
mentioning
confidence: 99%